Factor x^3-4x^2+5x-2 and 27a^3-64b^3

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to find the roots of polynomial `x^3-4x^2+5x-2 = 0` , hence you should find the divisors of the constant terms such that:

`D_2:{+-1;+-2}`

You need to substitute each of these divisors in polynomial to check if one of them cancels it.

Substituting -1 for x yields:

`(-1)^3 - 4*(-1)^2 + 5*(-1) - 2 != 0`

`-1 - 4 - 5 - 2 != 0`

Substituting 1 for x yields:

`(1)^3 - 4*(1)^2 + 5*(1) - 2 = 0`

`1 - 4 + 5 - 2 = -3 + 3 = 0`

Notice that x = 1 is a root of polynomial, hence you may use reminder theorem such that:

`x^3-4x^2+5x-2 = (x-1)(ax^2+bx+c)`

Opening the brackets yields:

`x^3-4x^2+5x-2 = ax^3 + bx^2 + cx - ax^2 - bx - c`

Equating coefficients of like terms yields:

`a=1`

`b-a=-4 =gt b-1=-4 =gt b=-3`

`c-b=5 =gt c+3=5 =gt c=2`

Hence, if `x^3-4x^2+5x-2 =(x-1)(x^2-3x+2)`  and `x^3-4x^2+5x-2 = 0` , then `(x^2-3x+2) = 0` .

You need to use quadratic formula to find the roots of equation `x^2-3x+2 = 0`  such that:

`x_(1,2) = (3+-sqrt(9-8))/2 =gt x_(1,2) = (3+-1)/2`

`x_1 = 2; x_2 = 1`

Hence, you need to write the factored form of polynomial `x^3-4x^2+5x-2`  such that: `x^3 - 4x^2 + 5x - 2 = (x - 1)^2(x - 2).`

You need to write the factored form of difference `27a^3-64b^3` , hence you may use the following formula of difference of cubes such that:

`x^3 - y^3 = (x-y)(x^2+xy+y^2)`

`27a^3-64b^3 = (3a - 4b)(9a^2 + 12ab + 16b^2)`

Hence, evaluating the factorized form of `27a^3-64b^3`  yields `27a^3-64b^3 = (3a - 4b)(9a^2 + 12ab + 16b^2).`

Approved by eNotes Editorial
An illustration of the letter 'A' in a speech bubbles

The expression `x^3-4x^2+5x-2` has to be factored.

`x^3-4x^2+5x-2`

=> `x^3 - x^2 - 3x^2 + 3x + 2x - 2`

=> `x^2(x - 1) - 3x(x - 1) + 2(x - 1)`

=> `(x^2 - 3x + 2)(x - 1)`

=> `(x^2 - 2x - x + 2)(x - 1)`

=> `(x(x - 2) - 1(x - 2))(x - 1)`

=> `(x - 1)(x - 2)(x - 1)`

=> `(x - 2)(x - 1)^2`

`27a^3 - 64b^3`

=> `(3a)^3 - (4b)^3`

=> `(3a - 4b)(9a^2 + 16b^2 + 12ab)`

The required factorized form of `x^3-4x^2+5x-2 = (x - 2)(x - 1)^2` and `27a^3 - 64b^3 = (3a - 4b)(9a^2 + 16b^2 + 12ab)`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial